2010
DOI: 10.1007/s00421-010-1654-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endurance training on performance and muscle reoxygenation rate during repeated-sprint running

Abstract: The aim of the present study was to examine the effect of an 8-week endurance training program on repeated-sprint (RS) performance and post-sprints muscle reoxygenation rate in 18 moderately trained males (34 ± 5 years). Maximal aerobic speed (MAS), 10 km running and RS (2 × 15-s shuttle-sprints, interspersed with 15 s of passive recovery) performance were assessed before and after the training intervention. Total distance covered (TD) and the percentage of distance decrement (%Dec) were calculated for RS. Bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
84
2
16

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 38 publications
8
84
2
16
Order By: Relevance
“…The effects of training and de-training on the recovery time constant of muscle trueV˙O2 measured by NIRS have also been shown in wrist flexor muscles 63 . Re-oxygenation rate following exercise is faster in trained individuals than in non-trained controls 28 and re-oxygenation rate can be improved by undertaking a training intervention 64 . Re-oxygenation is slower in patients with diseases affecting O 2 delivery, such as heart failure 65 but recently, exercise training has been shown to improve this reduction 45 …”
Section: Assessment Of Skeletal Muscle Truev˙o2mentioning
confidence: 94%
“…The effects of training and de-training on the recovery time constant of muscle trueV˙O2 measured by NIRS have also been shown in wrist flexor muscles 63 . Re-oxygenation rate following exercise is faster in trained individuals than in non-trained controls 28 and re-oxygenation rate can be improved by undertaking a training intervention 64 . Re-oxygenation is slower in patients with diseases affecting O 2 delivery, such as heart failure 65 but recently, exercise training has been shown to improve this reduction 45 …”
Section: Assessment Of Skeletal Muscle Truev˙o2mentioning
confidence: 94%
“…Alterations in tissue concentrations of oxy- [HbO 2 ], deoxy- [HHb] and total hemoglobin [tHb] were monitored with a portable near-infrared spectrophotometer (NIRS) (Portamon, Artinis Medical System, Zetten, the Netherlands) attached with a 10 x 10-cm adhesive patch across the widest girth of the left vastus lateralis muscle, as described previously [28]. The distance from the base of the patella along the vertical axis of the thigh to the center of this device was approximately 10 cm.…”
Section: Methodsmentioning
confidence: 99%
“…The tissue saturation index (TSI, expressed as % and calculated as [HbO 2 ]/([HbO 2 ] + [HHB]) x 100) provided an indicator of the equilibrium between oxygen supply and consumption. Previous findings have demonstrated that the TSI provides a more accurate indication of muscle oxygenation than [HHb] [28,30]. The absolute TSI values observed at 30 s, 60 s, 120 s and 180 s into each trial were used for statistical analysis and the increases in these values following 15 s, 30 s, 60 s, 120 s and 300 s of recovery were taken as indices of the rate of re-oxygenation [28,31].…”
Section: Methodsmentioning
confidence: 99%
“…To analyze a NIRS signal, single values for each sprint and recovery are typically determined for each peak and nadir . A mean is calculated over a predetermined duration within the closing seconds of each sprint and recovery periods to smooth fluctuations in raw NIRS data during sprint exercise .…”
Section: Introductionmentioning
confidence: 99%
“…A mean is calculated over a predetermined duration within the closing seconds of each sprint and recovery periods to smooth fluctuations in raw NIRS data during sprint exercise . This method has been used on numerous occasions in acute settings, varying inspired O 2 fraction, active vs passive rest, after respiratory muscle warm‐up, and in response to training . However, a possible drawback is that the true, physiological peak and/or nadir [HHb] may not fall within the predefined analysis window.…”
Section: Introductionmentioning
confidence: 99%